Wildcat wellness coaching feasibility trial: protocol for home-based health behavior mentoring in girls - Cull, Brooke J.; Rosenkranz, Sara K.; Dzewaltowski, David A.; Teeman, Colby S.; Knutson, Cassandra K.; Rosenkranz, Richard R. (My University, 2016)
Childhood obesity is a major public health problem, with one third of America’s children classified as either overweight or obese. Obesity prevention and health promotion programs using components such as wellness coaching and home-based interventions have shown promise, but there is a lack of published research evaluating the impact of a combined home-based and wellness coaching intervention for obesity prevention and health promotion in young girls. The main objective of this study is to test the feasibility of such an intervention on metrics related to recruitment, intervention delivery, and health-related outcome assessments. The secondary outcome is to evaluate the possibility of change in health-related psychosocial, behavioral, and biomedical outcomes in our sample of participants.
Citation: Cull, B. J., Rosenkranz, S. K., Dzewaltowski, D. A., Teeman, C. S., Knutson, C. K., & Rosenkranz, R. R. (2016). Wildcat wellness coaching feasibility trial: protocol for home-based health behavior mentoring in girls. Pilot and Feasibility Studies, 2(1), 26. https://doi.org/10.1186/s40814-016-0066-y
Keywords: Children; Primary prevention; Role modeling; Social cognitive theory; Motivational interviewing